Coassembly of hypoxia-sensitive macrocyclic amphiphiles and extracellular vesicles for targeted kidney injury imaging and therapy - Yuan-Qiu Cheng; Yu-Xin Yue; Hong-Mei Cao; Wen-Chao Geng; Lan-Xing Wang; Xin-Yue Hu; Hua-Bin Li; Qiang Bian; Xiang-Lei Kong; Jian-Feng Liu; De-Ling Kong; Dong-Sheng Guo; et al. (Journal of Nanobiotechnology, 2021)
Abstract Background Hypoxia is a major contributor to global kidney diseases. Targeting hypoxia is a promising therapeutic option against both acute kidney injury and chronic kidney disease; however, an effective strategy that can achieve simultaneous targeted kidney hypoxia imaging and therapy has yet to be established. Herein, we fabricated a unique nano-sized hypoxia-sensitive coassembly (Pc/C5A@EVs) via molecular recognition and self-assembly, which is composed of the macrocyclic amphiphile C5A, the commercial dye sulfonated aluminum phthalocyanine (Pc) and mesenchymal stem cell-excreted extracellular vesicles (MSC-EVs). Results In murine models of unilateral or bilateral ischemia/reperfusion injury, MSC-EVs protected the Pc/C5A complex from immune metabolism, prolonged the circulation time of the complex, and specifically led Pc/C5A to hypoxic kidneys via surface integrin receptor α4β1 and αLβ2, where Pc/C5A released the near-infrared fluorescence of Pc and achieved enhanced hypoxia-sensitive imaging. Meanwhile, the coassembly significantly recovered kidney function by attenuating cell apoptosis, inhibiting the progression of renal fibrosis and reducing tubulointerstitial inflammation. Mechanistically, the Pc/C5A coassembly induced M1-to-M2 macrophage transition by inhibiting the HIF-1α expression in hypoxic renal tubular epithelial cells (TECs) and downstream NF-κB signaling pathway to exert their regenerative effects. Conclusion This synergetic nanoscale coassembly with great translational potential provides a novel strategy for precise kidney hypoxia diagnosis and efficient kidney injury treatment. Furthermore, our strategy of coassembling exogenous macrocyclic receptors with endogenous cell-derived membranous structures may offer a functional platform to address multiple clinical needs. Graphical Abstract